Svobodní lidé? Svoboda pohybu bývalých nevolníků v Rakousku 1781–1848 (na příkladu lichtenštejnských dominií) - Zdeňka Stoklásková (Studia Historica Brunensia, 2019)
This paper attempts to answer the question concerning the degree to which the position of serfs changed after the abolition of serfdom in Austria. Were the people in fact free as has been stated time and again in the history books and textbooks? Research into two Liechtenstein estates – the South Moravian domain of Břeclav/Lundenburg and the Lower Austrian estate of Wilfersdorf was used to analyse the factors behind personal freedom of movement after the abolition of serfdom. Could former serfs travel freely to other estates or abroad? This narrow study showed that this was not the case until the end of the pre-March period, i.e. after the end of patrimonial administration. These findings go against traditional interpretations. The abolition of serfdom was undoubtedly a step towards a modern society, but its implementation did not result in the end of control mechanisms, as they were replaced by others, and not only in the developing legal system. A lesser-known new factor from the period was the restriction of demesnial jurisdiction, which was placed under the control of the regional authorities. However, the period of reform did usher in a new phenomenon: the legal right of former serfs to protection against seignorial powers.